New methods in diagnosis and therapy Beneficial triple-site cardiac resynchronization in a patient supported with an intra-aortic balloon pump for end-stage heart failure - Ciszewski, Jan; Maciąg, Aleksander; Gepner, Katarzyna; Smolis-Bąk, Edyta; Sterliński, Maciej (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
The authors present the case of a 62-year-old male patient with an implantable cardioverter-defibrillator  and end-stage heart failure supported with an intra-aortic balloon pump. Implantation of a triple-site cardiac resynchronization system and complex heart failure treatment brought a significant improvement, return to home activity and 17-month survival. The patient died due to heart failure aggravation. Within this time he was rehospitalized and successfully treated twice for an electrical storm.